Lattice Sphere Detection Techniques In Block Data Transmission And Multiuser Wireless Systems - Albreem, Mahmoud A. M. (2013)
Recent years have witnessed an increase in demand for higher transmission data rates for wireless multimedia communications applications. Block Data Transmission Systems (BDTS) and Code Division Multiple Access (CDMA) are considered as efficient techniques for high data rate transmission and found in the coming generation of mobile and wireless technologies such as Long Term Evolution (LTE) systems. The Exhaustive Search (ES) detector is the optimum. Owing to its high computational load, lattice sphere detection (LSD) technique and its variants had been proposed. For the system designer, the main objective is to achieve an attractive performance-complexity tradeoff. In this research, LSD based detectors are designed for BDTS and Multi-User Detection (MUD) system. LSD searches lattice points in a sphere within a predetermined radius. In LSD, when the initial radius increases, the performance and complexity increased. This research produces exact expression for the sphere radius used in LSD technique which depends on the lattice dimension and average received power. It is well known fact that a small condition number results in a better detection performance. This research aims to reduce the condition number value to its smallest possible using the regularization methods (L1-regularization and L2-regularization), and utilizing special matrices (i.e., Hankel and Toeplitz). Sequentially, this research proposed a new detection technique which called as a near-An-LSD technique. Exact relationships between the LSD performance and condition number, and the relationship between the radius and condition number had been derived.